Информационный тоталитаризм: реальность и опасность современной эпохи - Цыбулько, В. И. (ХНУРЭ, 2012)
The given work is devoted to the questions of informatization process in the modern man’s life. The prospects of using an acquisitions of the information society in cooperation with the authorities, the question of collisions Informatization and totalitarianism are reviewed.